2002
DOI: 10.1126/science.1069525
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cachexia in Mice by Systemically Administered Myostatin

Abstract: Mice and cattle with genetic deficiencies in myostatin exhibit dramatic increases in skeletal muscle mass, suggesting that myostatin normally suppresses muscle growth. Whether this increased muscling results from prenatal or postnatal lack of myostatin activity is unknown. Here we show that myostatin circulates in the blood of adult mice in a latent form that can be activated by acid treatment. Systemic overexpression of myostatin in adult mice was found to induce profound muscle and fat loss analogous to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
702
2
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 818 publications
(744 citation statements)
references
References 28 publications
29
702
2
11
Order By: Relevance
“…, 2000; Langley et al. , 2002) and overexpression of Mstn in vivo results in cachexia in mice (Zimmers et al. , 2002; Reisz‐Porszasz et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2000; Langley et al. , 2002) and overexpression of Mstn in vivo results in cachexia in mice (Zimmers et al. , 2002; Reisz‐Porszasz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin has both paracrine and endocrine effects (Zimmers et al. 2002), although it is the endocrine function which appears key for regulation of muscle mass, due to an observed inverse correlation with muscle mass in humans (Gonzalez‐Cadavid et al. 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the authors, using healthy university students, showed significantly increased levels of myostatin mRNA in muscle tissue after the unilateral suspension of a hindlimb for two weeks. In addition, administration of myostatin in vivo to adult mice induceed profound muscle loss analogous to that seen in human cachexia syndrome 117) . Together these studies suggest that increased levels of myostatin lead to muscle wasting.…”
Section: Myostatin -The Other Modulator Of Muscle Regenerationmentioning
confidence: 95%
“…When produced in Chinese hamster ovary cells, the C-terminal dimer remains bound to the N-terminal propeptide (NTPP), which remains in a latent, inactive state 116) . Most, if not all, of the myostatin protein that circulates in blood, also appears to exist in an inactive complex with a variety of proteins, including propeptides 117) .…”
Section: Myostatin -The Other Modulator Of Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation